The Influence of Profitability and Liquidity on Company Value through Capital Structure in Food and Beverage Sector Companies on the Indonesia Stock Exchange - Syahridlo, Muhammad Dio; Pertiwi, Tri Kartika; Nur, Dhani Ichsanuddin (Indonesian Journal of Advanced Research, 2025)
One of the key measures of a business's performance is its value; a high valuation indicates that investors are confident in the company's potential for future growth.  This study aims to examine the following factors: (1) the impact of profitability on company value; (2) the impact of liquidity on company value; (3) the impact of profitability through capital structure; and (4) the impact of liquidity on company value in companies in the food and beverage sector listed on the Indonesia Stock Exchange.  This study employs a path analysis method in conjunction with a quantitative methodology.  Purposive sampling was utilized in the data gathering process, and 31 companies in the food and beverage industry that were listed on the Indonesia Stock Exchange between 2020 and 2023 made up the sample. The study's findings indicated that a company's value is influenced by its profitability.  A company's liquidity adds to its worth.  Through its capital structure, profitability adds to a company's worth.  Through its capital structure, liquidity adds to a company's worth.